Local Expression of Interleukin-17a is Correlated with Nasal Eosinophilia and Clinical Severity in Allergic Rhinitis. Issue 1 (March 2014) - Makihara, Seiichiro; Okano, Mitsuhiro; Fujiwara, Tazuko; Noda, Yohei; Higaki, Takaya; Miyateke, Tomomi; Kanai, Kengo; Haruna, Takenori; Kariya, Shin; Nishizaki, Kazunori
Interleukin (IL)-17A is a major cytokine produced by Th17 cells, which are associated with chronic inflammations. The local expression of IL-17A in allergic rhinitis (AR) remains to be characterized. We sought to determine the role of IL-17A expression in human inferior turbinate mucosa in the pathophysiology of AR. Inferior turbinate mucosa was sampled from medical treatment-resistant, surgery-required patients with perennial AR (PAR, n = 21), nonallergic rhinitis with eosinophilia syndrome (NARES, n = 7), and nonallergic hypertrophic rhinitis (HR, n = 13). IL-17A expression was determined with immunohistochemical staining. The mean number of IL-17A + cells and eosinophils per field were counted. Total serum immunoglobulin E (IgE) levels, blood eosinophil count, and forced expiratory volume in 1 second (FEV1 )/forced vital capacity (FVC) ratio were also examined in each patient. IL-17A was primarily expressed in infiltrating inflammatory cells. The number of IL-17A + cells in nasal mucosa was significantly higher in the PAR group compared with HR (p = 0.002) and NARES (p = 0.021) groups. There was a significant and positive correlation between the number of IL-17A + cells and total nasal symptom score (rho = 0.403; p = 0.011), especially sneezing score (rho = 0.471; p = 0.003). The number of IL-17A + cells was significantly and positively correlated with the degree of eosinophil infiltration (rho = 0.623; p < 0.001), but not with total serum IgE levels (rho = 0.284; p = 0.098), blood eosinophil counts (rho = 0.302; p = 0.056), or FEV1 /FVC ratio (rho = 0.092; p = 0.569). The present study provides evidence that IL-17A expression in the nasal mucosa is associated with the pathophysiology of AR, including disease severity and nasal eosinophilia.